International cooperation tedencies of non-governmental organizations working for Syrian Refugees in Istanbul - Bayraktar, Merve Nur (My University, 2021)
Bugün, Türkiye’de yaşayan 3.6 milyon Suriyeli mülteci, Türkiye-AB ilişkilerini oluşturan en önemli başlıklardan biridir. Suriyelilerin yeniden yerleştirilmeleri konusunda, devlet aktörlerinin yanı sıra sivil toplum kuruluşlarının da (STK) aktif rol oynadığı bilinmektedir. Bu amaç doğrultusunda çalışan sivil toplum kuruluşlarının bazılarının uluslararası kuruluşlarla işbirliği halinde çalışırken bazılarının da bu kuruluşlardan destek almadığı gözlemlenmiştir. Suriyeli mültecilere destek veren STK’ların çalışma yöntemlerindeki bu farklılığın sebebini anlamak için mülteci çalışmalarını sürdüren farklı STK’larla görüşmeler yapılmıştır. İçerisinde en fazla mülteci derneğinin bulunduğu şehir olan İstanbul’dan 13 STK seçilmiş ve her biri ile yaklaşık birer saat süren görüşmeler yapılmıştır. Kasım 2020’de başlayan görüşmeler, Nisan 2021’de sona ermiş; görüşme kayıtları nitel analiz yöntemi ile incelenmiştir. STK’ların uluslararası kuruluşlarlarla işbirliği kurma davranışını belirleyen temel unsurların kurumsal kapasite ve işbirliği yapmak ya da yapmamak yönündeki kurumsal politika ile alakalı olduğu tespit edilmiştir.

Currently, 3.6 million Syrian refugees in Turkey are one of the most crucial topics in sense of Turkey-EU relations. It is known that state actors as well as non-governmental organizations (NGOs) play an active role in Syrians’ resettlement process. In that regard, it has been observed that whereas some of the NGOs working for this purpose work in cooperation with international organizations, others do not receive any support from such organizations. In order to understand the reason for this difference in NGOs’ –which support Syrians- manners of work, interviews were carried out with different NGOs that continued their refugee-based work. 13 NGOs were selected from Istanbul, the city with the largest refugee associations, and each of them held interviews lasting about one hour. The interviews that began in November 2020 ended in April 2021 and interview records were evaluated by qualitative analysis method. Therefore, it has been determined that the main elements that determine the behavior of NGOs to cooperate with international organizations are related to institutional capacity and institutional policy regarding cooperation.
Keywords: Forced Migration; International Cooperation; International relations; Political science; Sivil Toplum Kuruluşları; Siyasal bilim; Suriyeli Mülteciler Civil Society Organizations; Syrian Refugees; Uluslararası ilişkiler; Uluslararası İşbirliğii; Zorunlu Göç